ANALISIS KUALITAS PELAYANAN PUBLIK PADA KANTOR KELURAHAN KUALA JELAI KECAMATAN JELAI KABUPATEN SUKAMARA: ANALYSIS OF THE QUALITY OF PUBLIC SERVICESOFFICE KELURAHAN KUALA JELAI, KECAMATAN JELAI, SUKAMARA DISTRICT - Mu'ti, Abdul; Bernardianto, Raden Biroum; Sion, Holten (Pencerah Publik, 2022)
The Kuala Jelai Urban Village, Jelai District, Sukamara Regency has a function of providing public services in accordance with existing SOPs to ensure optimal quality service. This study of the service quality of the kelurahan office aims to analyze the service quality of the Kuala Jelai Kelurahan Office. This research was conducted with a qualitative descriptive approach, with interview data collection methods and field observations. Research informants consisted of personnel from the Kuala Jelai Kelurahan Office as service providers and several communities as service recipients determined by purposive sampling. Research studies that are based on 5 (five) dimensions of service, namely: 1). Tangible variable dimensions. 2). Dimensions of the Reliability variable. 3). Responsiviness variable dimensions. 4). Assurance variable dimensions. 5). The Emphaty variable dimension shows 4 (four) variables included in the "very good" category (Reliability, Responsiveness, Assurance and Emphaty dimensions) while 1 (one) dimension is included in the "less good" category, namely the Tangible dimension. The study concluded that the services at the Kelurahan Kuala Jelai, Jelai District were classified as good qualifications and quality.